Prinsip Kepastian Hukum Dalam Penyelenggaraan Rumah Sakit Di Indonesia - Gustafianof, Gustafianof; Irham, Muhammad; Taufik, Iqbal (Bacarita Law Journal, 2024)
Hospital administrators' services should be directed towards their goals, but in reality this is not always the case. For this reason, implementation behavior must be able to be measured through legal regulations. This article has discovered the principle of legal certainty for good hospital management in Indonesia. Using normative legal research methods, the principle of legal certainty in the administration of hospitals in Indonesia is found through division of labor by specializing the work of medical staff and corporate staff using the same methods and procedures which are guided by the principles: (1) Division clear work; (2) Condition factors of the community served; (3) humanitarian goals and equality before the law; (4) Hospital By Laws which are guided and based on and in accordance with the values ​​of Pancasila and the 1945 Constitution which consist of corporate by laws, medical staff by laws, Nurse By Laws and Other Health by laws, which have so far been only corporate by laws and medical staff by laws. These principles should be made positive, so that benefit and justice for all parties can be realized for the sake of legal certainty for better health services in hospitals in Indonesia.